Intracranial translucency as a sonographic marker for detecting open spina bifida in the first trimester - Sawsan Zakariya Sulaiman; Medya Ghazi Sedeq (Zanco Journal of Medical Sciences)
Background and objective: Neural tube defect is a serious congenital anomaly associated with lifelong disability, mortality and morbidity; it consists of heterogeneous group of disorders affecting brain and spinal cord. This study aimed to test the efficacy and accuracy of the intracranial translucency (fourth ventricle) in diagnosing open spina bifida.